Training on making environmentally friendly soap from soap nuts and bengle essential oil in Gajahmungkur District - Ika Buana Januarti; Laily Mega Rahmawati (Community Empowerment, 2024)
The UNISULLA Pharmacy service team collaborated with the PAC GP Ansor of Gajahmungkur District to conduct community service activities aimed at enhancing public awareness of making environmentally friendly laundry soap from soap nuts and bengle essential oil. The activity was conducted in several stages, including a pre-test, education, training, and a post-test. This activity successfully increased participants knowledge and skills in making natural soap significantly by 100%. This initiative benefits the environment and has the potential to improve community welfare through the development of small and medium enterprises based on local resources.